Negotiating meaning in English as a lingua franca: IISMA awardees across Asian and European contexts - Fathina Shaliha; Isti Gandana (Teaching English as a Foreign Language Journal, 2026)
In line with the global trend of the internationalization of higher education, students are increasingly seeking educational experiences abroad. In this context, English as a lingua franca (ELF) plays a key role in navigating multilingual and multicultural environments. This study examines the experiences of six Indonesian students participating in the International Student Mobility Awards (IISMA) program, focusing on their use of ELF in Asian and European contexts. Using a qualitative case study design, with data collected through individual interviews and focus group discussion, the study highlights that familiarity with the host country’s language and cultural knowledge contribute to participants’ ability to communicate effectively. Participants’ experiences indicate the development of intercultural competence as they navigated linguistic and cultural differences. Two main themes emerged: (1) meaning-making through multilingual resources, and (2) negotiating understanding and misunderstanding in ELF contexts. The study offers implications for international education programs, particularly in strengthening language support and intercultural preparation to better equip students for global academic and social engagement.